2003
DOI: 10.1007/s00467-003-1067-7
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular dysfunction in α-thalassemia

Abstract: Shortened red cell life span and excess iron cause functional and physiological abnormalities in various organ systems in thalassemia patients. In an earlier study, we showed that β-thalassemia patients have a high prevalence of renal tubular abnormalities. The severity correlated with the degree of anemia, being least severe in patients on hypertransfusion and iron chelation therapy, suggesting that the damage might be caused by the anemia and increased oxidation induced by excess iron deposits. This study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
2
19
0
1
Order By: Relevance
“…Several authors have reported abnormalities of renal tubular function in patients with thalassaemia major and intermedia, such as proteinuria, hypercalciuria, and hyperphosphaturia as well as increased urinary excretion of markers of tubular injury, such as N-acetyl-b-D-glycosaminidase, malondialdehyde, and b 2 -microglobulin. (Sumboonnanonda et al, 1998(Sumboonnanonda et al, , 2003Aldudak et al, 2000;Koliakos et al, 2003;Mohkam et al, 2008;Sadeghi-Bojd et al, 2008;Smolkin et al, 2008) Our findings of hypercalciuria, albuminuria, proteinuria, and excretion of b 2 -microglobulin are in accordance with prior reports of renal tubular dysfunction. However, these studies all reported normal GFR.…”
Section: Discussionsupporting
confidence: 92%
“…Several authors have reported abnormalities of renal tubular function in patients with thalassaemia major and intermedia, such as proteinuria, hypercalciuria, and hyperphosphaturia as well as increased urinary excretion of markers of tubular injury, such as N-acetyl-b-D-glycosaminidase, malondialdehyde, and b 2 -microglobulin. (Sumboonnanonda et al, 1998(Sumboonnanonda et al, , 2003Aldudak et al, 2000;Koliakos et al, 2003;Mohkam et al, 2008;Sadeghi-Bojd et al, 2008;Smolkin et al, 2008) Our findings of hypercalciuria, albuminuria, proteinuria, and excretion of b 2 -microglobulin are in accordance with prior reports of renal tubular dysfunction. However, these studies all reported normal GFR.…”
Section: Discussionsupporting
confidence: 92%
“…Also, we found in thalassemia patients, S TAC was significantly positively correlated with eGFR, negatively with S Cys , S Cr and U MDA /Cr was positive significant correlation with each of U NAG /Cr, U β2MG /Cr and U albumin /Cr. This emphasis the role of oxidative stress in inducing renal tubular damage [5,38,39]. Although severe anemia and chronic hypoxia are believed to play a role in renal involvement in βTM, lipid peroxidation is currently the most favored hypothesis: according to this hypothesis, the imbalance in synthesis of hemoglobin (Hb) leads to excess unpaired globin chain and high intracellular content of non-Hb iron.…”
Section: Discussionmentioning
confidence: 99%
“…The unstable Hb subunits are known to generate free oxygen radical species that starting a chain of oxidative events which leading to disintegration of denatured globin chains, heme, and iron, which bind to different membrane proteins and altering their normal structure and functions. In addition, the excess free iron is known to be a catalyst of lipid peroxidation via the fenton reaction [39]. …”
Section: Discussionmentioning
confidence: 99%
“…In thalassemic patients, the increased intracellular content of non-hemoglobin iron generates free oxygen radicals that bind to different membrane proteins, altering the morphology, function, and structure of membrane proteins [80]. Free iron can also directly catalyze lipid peroxidation by removing hydrogen atoms from the fatty acids that constitute the lipid bilayer of organelles [81].…”
Section: Introductionmentioning
confidence: 99%